Diversity of capsaicin content, quantitative, and yield components in chili (Capsicum annuum) genotypes and their F1 hybrid - Zulfikar D Sahid; MUHAMAD SYUKUR; AWANG MAHARIJAYA (Society for Indonesian Biodiversity, 2020)
Abstract. Sahid ZD, Syukur M, Maharijaya A. 2020. Genetic diversity of capsaicin content, quantitative, and yield component in chili (Capsicum annuum) and their F1 hybrid. Biodiversitas 21: 2251-2257. Chili (Capsicum annuum L.) is one of the horticultural plants that have many benefits. The benefit of chili was determined by pungency level of its fruit. Pungency level of the chili is due to the capsaicin content in fruit. Information about the genetic diversity of capsaicin is still rarely available. The aims of this study were to obtain diversity information on quantitative, yield component, and capsaicin content, and to analyze the correlation among chili genotypes based on their morphological characters. This study used Randomized Complete Block Design with three replications. The genetic material used in this study consisted of 21 genotypes consisting of 6 genotypes of chili elders and 15 hybrid F1 genotypes resulting from their crossing. Six genotypes of the chili parents are C5, F6074, F9160291, Yuni, Bara, and Giant. 15 hybrid F1 genotypes used in this study are C5 x Bara, C5 x F6074, C5 x Yuni, C5 x Giant, C5 x F9160291, Bara x F6074, Bara x Yuni, Bara x Giant, Bara x F9160291, F6074 x Yuni, F6074 x Giant, F6074 x F9160291, Yuni x Giant, Yuni x F9160291, and Giant x F9160291. The observation was made on the variables of quantitative, yield, and capsaicin components on chili. The results showed that the highest capsaicin content only was found in Bara x F9160291. The results of scatterplot analysis showed that the highest capsaicin and yield component was found in BaraxF6074 and C5 x Yuni genotype. The results of cluster analysis showed that chili was clustered into three color groups. The character of capsaicin content is negatively correlated and very different from fruit weight, fruit diameter, fruit length, thick fruit flesh, total amount of fruit per plant, and fruit weight per plant.